Pengaruh Beban Operasional Pendapatan Operasional, Financing To Deposit Ratio, dan Non Performing Finance Terhadap Return On Asset pada Perusahaan Sektor Bank Umum Syari’ah di Indonesia Tahun 2018 – 2024 - Akhilah Putri Fariyanah Fadiya Hayyah; Anita Handayani (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study was conducted to determine the asset management and effectiveness of Islamic commercial banks in managing customer funds, through the Return On Asset financial ratio. Based on data from the Financial Services Authority, there are 14 companies in the Islamic Commercial Bank sector in Indonesia. The research method used quantitative analysis with a sample of 8 Islamic Commercial Banks. Sampling was conducted using purposive sampling, resulting in a dataset of 56 data points. The data processing tool used was multiple linear regression using the SPSS 25 program. The study results indicate that Operating Expenses to Operating Income (BOPO) has a significant impact on Return on Assets, Financing to Deposit Ratio (FDR) has a significant impact on Return on Assets, Non-Performing Finance (NPF) does not have a significant impact on Return on Assets, and there is a significant simultaneous effect of Operating Expenses to Operating Income, and Financing to Deposit Ratio, as well as Non-Performing Finance on Return on Assets.